Digital Marketing for Village Tourism - Wisudani Rahmaningtyas; Ratieh Widhiastuti; Hanna Netti Purasani; Ajie Pangestu; Rusdiana Rusdiana (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The purpose of this service activity is to provide knowledge about the importance of digital marketing in the era of industry 4.0, as well as provide direct training on making videos as a medium for promotion. The object of the service activity is the entire Management of Omah Smart Farmers Tourism Object (OPP) Kandri Tourism Village and Tourism Awareness Group Managers (Pokdarwis) Semarang City. Service activities are carried out in three stages, namely the preparation stage, the implementation stage, and the evaluation monitoring stage. The results of the service activities consist of the preparation stage in the form of coordination with the Head of the Kandri Tourism Village to find out the problems that exist in the Kandri Tourism Village. The service activity was considered successful, as evidenced by the implementation stage of all participants who were targeted to attend and were very enthusiastic in asking questions during the training. Many participants asked for advice in determining the right material to promote, and various tricks to get interesting promotional media. At the monitoring stage, the service team communicates through social media to find out the development of service activities. And the evaluation stage is carried out by asking for feedback from service participants as the basis for improving further service activities. the service team communicates through social media to find out the development of service activities. And the evaluation stage is carried out by asking for feedback from service participants as the basis for improving further service activities. the service team communicates through social media to find out the development of service activities. And the evaluation stage is carried out by asking for feedback from service participants as the basis for improving further service activities.